The Influence of Hedonic Shopping Motivation, Flash Sales, and Twin Date Promotions on Impulse Buying of Miniso Products on TikTok Shop among University Students in Surabaya - Theresa Arum Viadollorosa; Sugeng Purwanto (PT Larva Wijaya Penerbit, 2026)
This study aims to analyze the effect of hedonic shopping motivation, flash sale, and Twin Date promotion on impulse buying behavior of Miniso products on TikTok Shop among university students in Surabaya. This research employs a quantitative approach using a purposive sampling technique involving 180 respondents. Data processing and analysis were conducted using SmartPLS 4.0. The results indicate that hedonic shopping motivation, flash sale, and Twin Date promotion have a positive and significant effect on impulse buying. These findings highlight the importance of digital promotional strategies and consumer behavior understanding in enhancing impulsive purchasing behavior.